Reporting standards for guideline-based performance measures. (December 2015) - Nothacker, Monika; Stokes, Tim; Shaw, Beth; Lindsay, Patrice; Sipilä, Raija; Follmann, Markus; Kopp, Ina
Abstract Background The Guidelines International Network (G-I-N) aims to promote high quality clinical guideline development and implementation. Guideline-based performance measures are a key implementation tool and are widely used internationally for quality improvement, quality assurance, and pay for performance in health care. There is, however, no international consensus on best methods for guideline-based performance measures. In order to address this issue, the G-I-N Performance Measures Working Group aimed to develop a set of consensus-based reporting standards for guideline-based performance measure development and re-evaluation. Methods Methodology publications on guideline-based performance measures were identified from a systematic literature review and analyzed. Core criteria for the development and evaluation process of guideline-based performance measures were determined and refined into draft standards with an associated rationale and description of the evidence base. In a two-round Delphi-process, the group members appraised and approved the draft standards. After the first round, the group met to discuss comments and revised the drafts accordingly. Results Twenty-one methodology publications were reviewed. The group reached strong consensus on nine reporting standards concerning: (1) selection of clinical guidelines, (2) extraction of clinical guideline recommendations, (3) description of the measure development process, (4) measure appraisal, (5) measure specification, (6) description of the intended use of the measure, (7) measure testing/validating, (8) measure review/re-evaluation, and (9) composition of the measure development panel. Conclusions These proposed international reporting standards address core components of guideline-based performance measure development and re-evaluation. They are intended to contribute to international reporting harmonization and improvement of methods for performance measures. Further research is required regarding validity, acceptability, and practicality.